ANALISIS YURIDIS PUTUSAN HAKIM TENTANG TINDAK PIDANA MENGGUNAKAN, MENGUASAI, DAN MENYEDIAKAN NARKOTIKA GOLONGAN I BUKAN JENIS TANAMAN(STUDI KASUS TERHADAP PUTUSAN PENGADILAN NEGERI KUPANG NOMOR 193/Pid.Sus/2022/PN KPG) - Wara, Charlos Constantinus; Pello, Jimmy; Manuain, Orpa Genefo (Petitum Law Journal, 2024)
The problem of misuse of Narcotics, Psychotropics and other Addictive Substances (NEPZA) or the popular term known by the public as Narcotics is a very big problem faced by society, government and law enforcement officials. In handling narcotics cases at the Kupang District Court, judges as law enforcers have the responsibility to examine, decide and resolve cases at the first instance. The main problem of this research is: What is the basis of the judge's legal considerations in handing down sentences against convicts in the case of District Court Decision NUMBER 193/Pid.Sus/2022/PN Kupang? And what should be the sanctions imposed on the perpetrators in District Court Decision NUMBER 193/Pid.Sus/2022/PN Kupang? This research focuses on two main issues, the basics, namely the judge's legal considerations and the sanctions that should be imposed, the method used in this research is a type of normative research, where the author obtains data indirectly or through an inventory of positive law, legal principles and doctrine, books -books and other documents. The research location is at the Law Library of Nusa Cendana University, Kupang. The legal materials used in this research are secondary legal materials. The data collection technique in this research was carried out using literature study. The data analysis used is normative analysis. The research results show that: There are two basic legal considerations for judges in deciding a case, namely legal considerations and non-juridical considerations. (a) Juridical considerations are the facts and testimony of witnesses in the trial. (b) Non-Judicial considerations include those that form the background to the action. The sanction that should be imposed on the defendant is that a criminal using narcotics violates the provisions of Article 127 of Law Number 35 of 2009 concerning Narcotics which is punishable by a maximum imprisonment of 4 (four) years. And narcotics abusers are required to undergo rehabilitation (Article 54 of Law Number 35 of 2009 concerning Narcotics). The fraudster's act of helping to sell narcotics belonging to Andri's brother fulfills the elements of Article 56 of the Criminal Code (helping to commit) which carries a criminal threat of being punished by the person involved (Andri's brother).